Putting the Right Question First (Analytic Teaching, 1987)
Introduction:  One little piece of literature, scarcely 30 pages long, includes the most compact formula for the whole process of teaching and learning that I've ever found.  It was written in 387 B.C.  The piece in Plato's dialogue, Meno, which ironically does not even directly deal with teaching and learning, but with virtue.  Midway in their discussion of this matter, however, Plato's characters Meno and Socrates are diverted by the issue of the nature of learning.  Socrates has advanced the notion that "what we call learning is merely recollection."  Naturally Meno asks him to explain this, and Socrates does so with a demonstration so precise that every teacher should read it carefully.